Further Flavonoids from Polygonum viscosum Buch-Ham. ex D. Don. (Polygonoceae) - Datta, Bidyut Kanti; Iasmin, Tahamina; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Three additional flavonoids such as 5,7,4?-trihydroxy-3,8,3?-trimethoxy flavonol (1), 5,7-dihydroxyflavone (chrysin, 2) and 5,6,7-trihydroxyflavone (baicalein, 3) were obtained from the methanol extract of whole plant of Polygonum viscosum. The structure of the isolated compounds was established exclusively by ultraviolet (UV) spectroscopy, mass spectrometry (MS) and a series of Nuclear Magnetic Resonance (NMR) analysis. Dhaka Univ. J. Pharm. Sci. 15(1): 27-30, 2016 (June)